Factors that Lead to Effective E-HRM Implementation in Nigeria Manufacturing Industry: (A Case Study on Dangote Cement) - Ahmed, Abdullahi Bida (2011)
Technology has now become the competitive tool around the globe. Technology has now become a competitive and strategic tool that is required in every organization or business. The way an organization or business can make use of technology determines how competitive it will be in its environment. The use of technology differs among countries, most especially in terms of develop and developing countries. Focusing on the developing countries, effort is always made to make sure technology is used to at least a particular capacity level. In the business environment E-HRM is a technology that plays important role in day to day activities. Businesses are making efforts to make E-HRM a basic requirement but this does not makes it easy most especially in the developing countries. Also in such countries established businesses are the ones mostly benefiting from such technology. Nigeria is a country always trying to make technology a basic necessity for their companies. Companies occur at different level and this research is focusing at other levels such as that of manufacturing sector in the country. In order to be precise, E-HRM will be focused on to see how such companies deal with such technology let alone the whole system. The research is focusing only on such aspect, and also giving the fact that such manufacturing sectors are the type of businesses that operate at a lower financial scale. Therefore the purpose of this research is to identify the possible factors that lead to effect implementation of E-HRM in Nigerian manufacturing industry. The research will consist of an introduction of both manufacturing industries and the Dangote cement which is the target of the research. A literature will be conducted which will serve as a guide for conducting the survey of the research, it will provide knowledge and ideas of past researchers which can be used for this study. A research framework will be developed to help answer the research questions and achieve the research objectives. Analysis of the survey is conducted to provide a conclusion to the research with a set of research hypotheses.